(untitled) (Archives of Mechanics - Test, 2022)
The present article deals with the propagation of inhomogeneous waves in an orthotropic medium based on Eringen’s nonlocal thermoelasticity. For chosen directions of propagation and a real finite inhomogeneity parameter, a complex slowness vector is specified to define the propagation of inhomogeneous incident wave. Then the reflection, transmission of plane waves at a plane interface between two nonlocal orthotropic thermoelastic halfspaces are discussed. In this incidence, horizontal slowness determines the slowness vectors for all reflected, transmitted waves. For each reflected, transmitted wave, the corresponding slowness vector is resolved to define its phase direction, phase velocity and attenuation angle. Appropriate boundary conditions on this wave-field determine the amplitude ratios for reflected, transmitted waves relative to the incident wave. The numerical examples are provided to show the effect of the inhomogeneity of incident wave, nonlocal parameter on the propagation characteristic of the reflected, transmitted waves.